2021
DOI: 10.1038/s41598-020-80198-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different combined regimens of cisplatin, metformin, and quercetin on nasopharyngeal carcinoma cells and subcutaneous xenografts

Abstract: Cisplatin, metformin, and quercetin are all reliable anticancer drugs. However, it is unclear how effective their different combination regimens are on the growth of nasopharyngeal carcinoma cell line Sune-1 and subcutaneous xenograft in nude mice. This study evaluated the effects of single-drug, two-drug, and three-drug simultaneous or sequential combined application of these drugs on the growth of Sune-1 cells and subcutaneous xenograft tumors in nude mice. The results showed that the different combination r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…An epidemiologic analysis based on three multicentric studies showed that metformin given for the treatment of diabetes is associated with longer overall survival of patients with HNSCC despite the negative prognostic impact of diabetes itself ( 57 ). In addition, it was demonstrated that the combination of metformin and cisplatin significantly improved the therapeutic effect of cisplatin in OSCC ( 58 ) and NPC ( 59 ). In contrast, another study found no significant prognostic impact of metformin in patients with HNSCC ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…An epidemiologic analysis based on three multicentric studies showed that metformin given for the treatment of diabetes is associated with longer overall survival of patients with HNSCC despite the negative prognostic impact of diabetes itself ( 57 ). In addition, it was demonstrated that the combination of metformin and cisplatin significantly improved the therapeutic effect of cisplatin in OSCC ( 58 ) and NPC ( 59 ). In contrast, another study found no significant prognostic impact of metformin in patients with HNSCC ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin-based chemotherapeutic regimens are applied as adjuvant treatments against OS patients, especially for malignancies with aggressive characteristics [12,13]. Notwithstanding, Cisplatin resistance is a significant hindrance to its clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…In epidemiological studies of head and neck cancer, diabetic patients treated with metformin had a lower risk of HNSCC than those who were not treated with metformin 11 . In addition, metformin potentiates the therapeutic effect of cisplatin on nonsmall-cell lung cancer 12 , breast cancer 13 , nasopharyngeal cancer 14 and oral squamous cell carcinoma 15 .…”
Section: Introductionmentioning
confidence: 99%